CXCR4 activation promotes differentiation of human embryonic stem cells to neural stem cells. (19th November 2016) - Zhang, Lijun; Hua, Qiuhong; Tang, Kaiyi; Shi, Changjie; Xie, Xin; Zhang, Ru
Highlights: The expression of CXCR4 increased dramatically in NSCs compared to hESCs. Activation of CXCR4 by agonist SDF-1 promoted differentiation of hESCs to NSCs. Antagonizing CXCR4 with antagonist postponed differentiation of hESCs to NSCs. Knockdown of CXCR4 in hESCs inhibited the neural induction process. Abstract: G protein-coupled receptors (GPCRs) are involved in many fundamental cellular responses such as growth, death, movement, transcription and excitation. Their roles in human stem cell neural specialization are not well understood. In this study, we aimed to identify GPCRs that may play a role in the differentiation of human embryonic stem cells (hESCs) to neural stem cells (NSCs). Using a feeder-free hESC neural differentiation protocol, we found that the expression of several chemokine receptors changed dramatically during the hESC/NSC transition. Especially, the expression of CXCR4 increased approximately 50 folds in NSCs compared to the original hESCs. CXCR4 agonist SDF-1 promoted, whereas the antagonist AMD3100 delayed the neural induction process. In consistence with antagonizing CXCR4, knockdown of CXCR4 in hESCs also blocked the neural induction and cells with reduced CXCR4 were rarely positive for Nestin and Sox1-staining. Taken together, our results suggest that CXCR4 is involved in the neural induction process of hESC and it might be considered as a target to facilitate NSC production from hESCs in regenerative medicine.